PENGARUH KENYAMANAN DAN TEPAT WAKTU TERHADAP KEPUASAN PASIEN BERSALIN PADA RSUD Dr. HAULUSSY DI KOTA AMBON - Herman Surijadi (Soso-Q : Jurnal Manajemen, 2019)
The purpose of this study was to examine and analyze the influence of service dimensions (comfort and on time) on maternity patient satisfaction at RSUD Dr. Haulussy. The population of this study were all maternity patients who were or had used services at Dr. Haulussy Ambon. Sampling uses a purposive sampling method so that the final sample size is 42 respondents. Analysis of research data using Multiple Linear Regression Analysis. The results showed that comfort and on time proved to have a positive and significant effect on patient satisfaction at the RSUD Dr. Haulussy. This can be proven through the regression coefficient which shows that if comfort and on time increase, then the increase will be followed by an increase in maternal patient satisfaction at RSUD Dr. Haulussy. Thus it can be said that increasing comfort and on time will increase the satisfaction of maternity patients in Dr. Haulussy. Keywords: Comfort, Timely, Satisfaction of Maternity Patients.